Institutional Determinants for Developing Corporate Crowdfunding - Elzbieta POHULAK-ZOLEDOWSKA (Communications of International Proceedings, 2023)
This article focuses on the regulation of investment crowdfunding as a key criterion for the dynamic but safe development of this form of business financing. The intensive, uncontrolled development of innovation in financial markets generally leads to irregularities (fraud, abuse, crises). In turn, excessive and restrictive regulation can act as a brake on the development of financial innovation. Due to the subject matter of the study, which is the regulation of equity crowdfunding as well as equity crowdfunding itself, the methodology of the study consists primarily of research of source data available online. A literature review of the regulation of innovation in financial services was conducted. This includes the identification and review of academic articles, research reports, books, industry publications and other authoritative sources. This synthesis of information helps to define an appropriate benchmark for the regulation of European crowdfunding, identifying patterns and challenges for effective, pro-development regulation. Author presents the equity crowdfunding regulations of the US and the UK - the world's number 1 and 2 crowdfunding markets - as a benchmark for the proposed pan-European regulations. The features of the common European rules seem to meet the requirements. And the increase of the funding amount to EUR 5 million opens up completely new possibilities for equity crowdfunding.
Keywords: equity crowdfunding; alternative finance; regulatioN